Phytochemical Screening and Pharmacological Assessment of Achyranthes Aspera L. Stem Extract as Anti-Inflammatory and Anti-Bacterial Potential - Baniya, Deepti Piya; Bohora, Sushmita; Giri, Usha; Bajracharya, Mijala; Raut, Sabita; Paudel, Roshan (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Achyranthes aspera L. (Dattiwan in Nepali), belongs to Amaranthaceae family is a medicinal herb of utmost importance which possess anti-bacterial, anti-fungal, anti-inflammatory, anti-spasmodic, astringent, diuretic activity and used for treatment of asthma, cough, diuretics, dental problems, etc. Method: A descriptive and experimental design was performed. Simple maceration process was carried for extraction. Quantitative phytochemical screening (Total Phenolic Content and Total Flavonoid Content) was conducted by Folin-Ciocalteu method and AlCl3 Colorimetric method respectively. In-vitro anti-inflammatory activity was performed by Human RBC membrane stabilization method and Anti-bacterial activity was carried out by Agar-well dilution method against Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae and Pseudomonas aeruginosa. Result: The qualitative phytochemical screening showed the presence of glycoside, flavonoid, saponin and reducing sugar in all three extracts whereas alkaloids and phenolic compounds were present only in ethanolic extract. The TPC of ethanolic extract was found to be 8.058 ±0.168 mg GAE/g. The TFC of aqueous, hydroalcoholic and ethanolic extract were 3.043 ±0.153, 6.23 ±0.042 and 45 ±0.720 mg QE/g respectively. All the three extracts showed significant anti-inflammatory activity, among them hydro-alcoholic extract showed the highest percent of membrane stabilization (i.e. 58.72%, 59.30%, 60.47%, 62.79% and 63.95% at 20, 40, 60, 80, 100 µg/ml concentration) as compared with Standard Diclofenac sodium. Ethanolic extract showed superior anti-bacterial activity against Gram-positive bacteria, showing Zone of Inhibition of 14.6, 16.1, 17.4 and 19.2 mm at 25, 50, 100 and 200 mg/ml respectively against Staphylococcus aureus and Zone of Inhibition of 9.1, 16.6, 18.1 mm at 50, 100, 200 mg/ml against Enterococcus faecalis respectively. Conclusion: The stem extracts of Achyranthes aspera L. showed presence of different phytoconstituents. The ethanolic extract of Achyranthes aspera L. showed higher anti-bacterial activity against Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis). The hydro-alcoholic extract exhibited superior anti-inflammatory activity whereas, other stem extracts of Achyranthes aspera L. showed minimal anti-inflammatory activity as compared to Diclofenac sodium.